Sodium intake combining cholinergic activation and noradrenaline into the lateral parabrachial nucleus. (6th August 2015) - Gasparini, S.; Andrade-Franzé, G.M.F.; Gomide, J.M.C.; Andrade, C.A.F.; De Luca, L.A.; Colombari, D.S.A.; De Paula, P.M.; Colombari, E.; Menani, J.V.
Highlights: Different mechanisms inhibit sodium intake in rats treated with cholinergic agonists. Pressor responses inhibit sodium intake in rats treated with cholinergic agonists. Noradrenaline in the LPBN deactivates inhibitory mechanisms for sodium intake. Noradrenaline in the LPBN does not deactivate cardiovascular inhibitory signals. Abstract: The administration of cholinergic agonists like pilocarpine intraperitoneally (i.p.) or carbachol intracerebroventricularly (i.c.v.) induces water, but non significant hypertonic NaCl intake. These treatments also produce pressor responses, which may inhibit sodium intake. Noradrenaline (NOR) acting on α2 -adrenoceptors in the lateral parabrachial nucleus (LPBN) deactivates inhibitory mechanisms increasing fluid depletion-induced sodium intake. In the present study, we investigated: (1) water and 1.8% NaCl intake in rats treated with pilocarpine i.p. or carbachol i.c.v. combined with NOR into the LPBN; (2) if inhibitory signals from cardiovascular receptors are blocked by NOR in the LPBN. Male Holtzman rats with stainless steel guide-cannulas implanted in the lateral ventricle and bilaterally in the LPBN were used. Bilateral injections of NOR (80 nmol/0.2 μl) into the LPBN decreased water intake (0.8 ± 0.3, vs. saline (SAL): 2.9 ± 0.3 ml/180 min) induced by pilocarpine (1 mg/kg of body weight) i.p., without changing 1.8% NaCl intake (0.8 ± 2.4, vs. SAL: 0.5 ± 0.3 ml/180 min). Prazosin (1 mg/kg of body weight) i.p. blocked pressor responses and increased water and 1.8% NaCl intake (6.3 ± 1.7 and 14.7 ± 3.5 ml/180 min, respectively) in rats treated with pilocarpine combined with NOR into the LPBN. Prazosin i.p. also increased 1.8% NaCl intake in rats treated with carbachol i.c.v combined with NOR into the LPBN. The results suggest that different signals inhibit sodium intake in rats treated with cholinergic agonists, among them those produced by increases of arterial pressure that are not efficiently deactivated by NOR acting in the LPBN.